Noise Risk Assessment Using Noise Mapping Analysis Method and Noise Control at a Steel Company in Cilegon - Rani Marfuah; Endah Dwi Handayani (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Physical factors found in the workplace can have an impact on occupational health and safety; one example of these physical factors is high noise intensity. One of the workplaces that have high noise intensity is a steel manufacturing company. The purpose of this study is to determine the noise risk based on noise mapping and analyse efforts that have been made in the Continous Tandem Cold Mill area in a steel company in Cilegon. Methods: The method used in this study was descriptive method. The variables used were the results of noise intensity measurements. The data were collected by means of literature study, field observation and noise measurements. The data obtained were then analysed using a descriptive method and were used as a basis in developing noise mapping. Results: Based on noise mapping, the welder area has the highest noise intensity of 91.1 - 94 dBA. Efforts to control noise intensity that have been carried out in the company are administrative control and personal protective equipment. Conclusion:From the results of noise intensity measurements in the Continous Tandem Cold Mill area of a steel company in Cilegon, it can be concluded that the measurement point is 76% - 100% and that the noise measurement points exceed the threshold value stipulated in the Regulation of the Minister of Manpower of the Republic Indonesia Number 5 of 2018. However, the steel company in Cilegon has made several efforts to reduce the noise intensity.Keywords: noise, noise mapping, steel company